New molecular and morphological data for opecoelid digeneans in two Mediterranean sparid fishes with descriptions of Macvicaria gibsoni n. sp. and M. crassigula (Linton, 1910) (sensu stricto) - Rima, Mohammed; Marzoug, Douniazed; Pérez-Del-Olmo, Ana; Kostadinova, Aneta; Bouderbala, Mohamed; Georgieva, Simona (Systematic parasitology, 2017)
Molecular and morphological data were gathered for specimens of species of Macvicaria Gibson & Bray, 1982 and Pseudopycnadena Saad-Fares & Maillard, 1986 (Digenea: Opecoelidae) collected from two sparid fishes, Diplodus vulgaris (Geoffroy Saint-Hilaire) and Sparus aurata L., off the Algerian coast of the Western Mediterranean. Phylogenetic analyses based on ITS1-5.8S-ITS2 and partial 28S rDNA sequences provided evidence for the distinct species status of eight Mediterranean species of Macvicaria. Novel molecular data are provided for four species, M. gibsoni n. sp. and M. crassigula (Linton, 1910) (sensu stricto) based on specimens from D. vulgaris, and M. mormyri (Stossich, 1885) and M. maamouriae Antar, Georgieva, Gargouri & Kostadinova, 2015 based on specimens from S. aurata; descriptions of the molecular voucher material of the former three species are provided. Two species were delineated within the "crassigula" species complex of Macvicaria, M. gibsoni n. sp. and M. crassigula (s. str.), the distinctive differentiating features being the distribution of the dorsal vitelline fields in the forebody, confluent in M. gibsoni n. sp. and non-confluent in M. crassigula (s. str.), and the molecular data for both markers. Sequences associated with morphological description are also provided for the type-species of Pseudopycnadena, P. fischthali Saad-Fares & Maillard, 1986, based on material from D. vulgaris.
Keywords: DNA, Ribosomal Spacer; Animals; Perciformes; druhová specificita; RNA ribozomální 28S; zvířata; DNA, Ribosomal; Phylogeny; fylogeneze; RNA, Ribosomal, 28S; ribozomální DNA; mezerníky ribozomální DNA; Species Specificity; Trematoda